Comparison of sugammadex vs. neostigmine use in recovery of muscle relaxation related to vecuronium in obesity surgery - Mete, Aslı; Karaduman, Simay; Sungurtekin, Hülya; Kılıç, Onur (Journal of Surgery and Medicine, 2019)
Aim: There are many methods in anesthesia to measure the recovery after the use of neuromuscular blocking agent. Monitoring the neuromuscular function can be used to identify the residual blocks. The importance of morbid obesity in anesthesia is caused by the difficulty in succeeding sufficiency of respiration and patency of airway. There are so many methods to measure the recovery when the neuromuscular blocking agent is used. Monitoring the neuromuscular function is used to identify the residual blocks. Methods: We designed a retrospective study with cross-sectional design. After power analysis 40 morbid obese patients operated with laparoscopic sleeve gastrectomy to treat the obesity, have been included in the study. 40 patients with sugammadex group S and neostigmine group were divided into two groups as equal. Results: In group S, there were 14 female and 6 male having the average of 33.25 ages and the average of body mass index (BMI) as 42.96. In group N, there were 16 women and 4 men having the average of 37.55 ages and the average of BMI as 42.96. While in group S the basal Train of four (TOF) value was 89.75%, in group N basal TOF was 90.65%. The duration of extubation in group S was measured 1 min and 40 sec but in group N it was measured 4 min and 39 sec. Also, the duration of recovery of muscle strength as an indicator of the recovery of basal TOF values was observed as 3 min and 15 sec in group S, and it was observed as 6 min and 18 sec in group N (P<0.001). The duration of extubation in group N was longer than in group S (P<0.001). Also, the duration of the recovery of basal TOF values as the duration of recovery of muscle strength was longer in group N than in group S (P<0.001). Conclusions: While in the study with rocuronium, the duration of recovery of muscle strength with sugammadex got shorter 4 times, in our study this duration was become shorter 2 times. It can be explained as the long effects of vecuronium.